Workplace interventions for increasing physical activity in employees: A systematic review. Issue 1 (9th September 2022) - Ramezani, Mozhdeh; Tayefi, Batool; Zandian, Elham; SoleimanvandiAzar, Neda; Khalili, Narjes; Hoveidamanesh, Soodabeh; Massahikhaleghi, Parissa; Rampisheh, Zahra
Abstract: Background: There is scattered evidence of the impact of workplace interventions in improving employees' physical activity. This systematic review was performed to evaluate the strategies of workplace interventions and their effectiveness, as reported in primary studies. Method: Primary experimental trials, both randomized controlled trials (RCTs) and non‐RCTs, which examined interventions to increase healthy adult employees' physical activity were included in this review. Studies in English or Persian published between 2009 and 2019 with access to full text of resources were considered. Google Scholar, PubMed, Web of Science, Scopus and Cochrane Library, ProQuest (Thesis) and World Health Organization Clinical Trial Registration Databases and Persian databases such as SID, Magiran, IranMedex, Irandoc were searched. All the stages of review were conducted based on PRISMA. RoB and ROBINS‐I were used to assess the risk of bias of the primary studies. Results: Thirty‐nine studies, with a total of 18 494 participants, met the inclusion criteria. Of these, 22 were RCTs, 17 were non‐RCTs. Effective interventions were reported in 15 RCTs and 14 non‐RCTs. Four main strategies of interventions were identified, consisting of motivation and support; monitoring and feedback; information and education; and activity. Thirteen different behavior change techniques (BCT) were identified with self‐determination theory (SDT) being the most frequent behavior change theory used. Conclusion: It seems that a multi‐strategy intervention that one of the strategies of which is physical activity in the workplace (Activity), the use of behavioral change theories, especially SDT, may be indicative of a more effective intervention. It is recommended that BCTs be considered when designing physical activity interventions.